2022
DOI: 10.3233/idt-210055
|View full text |Cite
|
Sign up to set email alerts
|

COV-ELM classifier: An extreme learning machine based identification of COVID-19 using chest X-ray images

Abstract: Coronaviruses constitute a family of viruses that gives rise to respiratory diseases. COVID-19 is an infectious disease caused by a newly discovered coronavirus also termed Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). As COVID-19 is highly contagious, early diagnosis of COVID-19 is crucial for an effective treatment strategy. However, the reverse transcription-polymerase chain reaction (RT-PCR) test which is considered to be a gold standard in the diagnosis of COVID-19 suffers from a high fals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Most previous methods divided the dataset into various ratios of training, testing, and validation, while other methods used cross‐validation. While considering cross‐validation, the preceding studies analyzed 10‐fold [44,49,67,70], 5‐fold [31,32,50,77,79], and 4‐fold [45] cross‐validation. Compared to 4‐fold cross‐validation, 10‐fold and 5‐fold cross‐validation provide better results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most previous methods divided the dataset into various ratios of training, testing, and validation, while other methods used cross‐validation. While considering cross‐validation, the preceding studies analyzed 10‐fold [44,49,67,70], 5‐fold [31,32,50,77,79], and 4‐fold [45] cross‐validation. Compared to 4‐fold cross‐validation, 10‐fold and 5‐fold cross‐validation provide better results.…”
Section: Resultsmentioning
confidence: 99%
“…One of the previous studies [88] used Inception, and its AUC reached 100%. The sensitivity of feature extraction using NASNet‐Large [38] is 100%, while the F1‐score using the COV‐ELM [70] method is 95%. In addition, in terms of accuracy, NASNetMobile [26] scored the highest, reaching 100%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They show that the implementation of parallel versions of the algorithm in the C language with the OpenBLAS, Intel MKL, and MAGMA libraries is more advantageous compared to the reference version of MATLAB. Afterward, Rajpal et al [106] addressed the problem of ELM-based COVID-19 classification (COV-ELM) into three classes: (1) COVID-19, (2) normal, and (3) pneumonia. The results showed that COV-ELM outperforms new-generation machine learning algorithms.…”
Section: Graphics Processing Unitmentioning
confidence: 99%